The effect of giving purslane plant extract (Portulaca oleracea) on commercial feed to increase the brightness of betta fish (Betta sp.) - Aina, Nurul; Putrinigtias, Andika; Komariyah, Siti (Acta Aquatica: Aquatic Sciences Journal, 2024)
Indonesia is one of the largest exporters of fresh and marine ornamental fish. However, several obstacles are faced by betta fish farmers, namely, such as poor colour quality, and low growth. There are various ways to improve colour quality, namely by adding pigment through feed. One of them is by utilizing purslane (Portulaca oleracea). This study aimed to analyse the effect of purslane plant extract (Portulaca oleracea) in increasing the brightness of the colour of betta fish (Betta sp.). The research method used in this study was a completely randomized design (CRD) method with 4 treatments 3 three replications. The treatments to be carried out were: P0 (100 g pellets), P1 (25 ml/100 g pellets), P2 (50 ml/100 g pellets) and P3 (75 ml/100 g pellets). Parameters observed: colour intensity, Absolute Length Growth, Absolute Weight Growth, and Survival rate (SR). The results of the study were that purslane extract from commercial pellet feed had a significant effect on the colour intensity of betta fish with a P3 dose of 75 ml/100 g pellet. In absolute length growth, the addition of purslane extract to commercial feed had a significant effect (p<0.05). For absolute weight growth and survival rate, no significant effect on betta fish.Keywords: Commercial Pellets; Purslane Extract; Siamese Fighting Fish